Performance-Based Design of Tall Timber Buildings Under Earthquake and Wind Multi-Hazard Loads: Past, Present, and Future - Tesfamariam, S. (Frontiers in Built Environment, 2022)
The rapid growth of the urban population and associated environmental concerns are challenging city planners and developers to consider sustainable and cost-efficient building systems. Timber-based buildings, such as sustainable systems, are increasingly used. The timber buildings, however, being lighter and flexible, can be vulnerable to earthquakes and wind loads. This paper gives a state-of-the-art review on performance-based design (PBD) considerations and future direction for timber and timber-based hybrid buildings. The PBD review covered both earthquake and wind loads and multi-hazard design considerations. The review also provided 1) current practice and future direction in consideration of hazard, response, and loss assessment within the multi-hazard PBD, 2) damping and energy dissipation devices, 3) optimization under uncertainty, and 4) future of surrogate and multi-fidelity modeling in PBD.